1989
DOI: 10.1002/ajmg.1320320417
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome mosaicism in 6,000 amniocenteses

Abstract: Multiple cell-multiple flask mosaicism was found in 0.20% of 6,000 amniocenteses, and multiple cell-single flask mosaicism was found in 0.92%. Multiple cell-multiple flask mosaicism usually was found in fetal or infant tissues at delivery or elective abortion. Most multiple cell-multiple flask mosaicism involved sex chromosomes and was either 45, X/46, XY or 45, X/46, XX. Except for one fetus with 45, X/46, XX and an aortic coarctation, phenotypic abnormalities associated with sex chromosome mosaicism were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 11 publications
3
18
1
Order By: Relevance
“…Data from several European countries with cytogenetic registries suggest that the great majority of TS cases are electively terminated [25][26][27], and so ability to assess clinical outcome is limited. Some early data which examined both abortuses and live births found that the great majority of 45,X/46,XY mosaic gestations resulted in phenotypically normal males [28,29]. A review of Danish registry cytogenetic data reported that as many as 1/250 (chorionic villous sampling) or 1/500 (amniocentesis) pregnancies of older mothers were diagnosed as TS [3].…”
Section: The Significance Of Prenatal Diagnosismentioning
confidence: 98%
“…Data from several European countries with cytogenetic registries suggest that the great majority of TS cases are electively terminated [25][26][27], and so ability to assess clinical outcome is limited. Some early data which examined both abortuses and live births found that the great majority of 45,X/46,XY mosaic gestations resulted in phenotypically normal males [28,29]. A review of Danish registry cytogenetic data reported that as many as 1/250 (chorionic villous sampling) or 1/500 (amniocentesis) pregnancies of older mothers were diagnosed as TS [3].…”
Section: The Significance Of Prenatal Diagnosismentioning
confidence: 98%
“…Mosaic Turner syndrome has a mild or absent phenotype at birth in 90% of cases and is associated with <10% of the fetal death rate associated with non-mosaic cases [Warburton et al, 1981]. Thus, its prevalence at the time of prenatal diagnostic sampling, (10-20 weeks gestation) is unlikely to be a great deal higher than the livebirth frequency [Hook and Warburton, 1983;Wilson et al, 1989]. While cases of mosaic Turner syndrome in fragile X full mutation females have been reported [Shapiro et al, 1994;Tejada et al, 1994;Wilkin et al, 2000], no increased prevalence of mosaic Turner syndrome in fragile X full mutation females was noted.…”
Section: Introductionmentioning
confidence: 98%
“…Mosaicism for trisomy 17 is a rare condition, which has been ascertained both pre-and postnatally. The few prenatally diagnosed cases have been observed in amniocytes (12 cases), [2][3][4][5][6][7][8] and, more rarely, in chorionic villus samples. 11 In all cases, no major foetal or newborn abnormalities were observed.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] No phenotypic abnormalities have been observed in the newborns or foetuses, and whenever additional cell types, mainly peripheral lymphocytes, were examined cytogenetically, these were shown to contain only euploid cells. On the other hand, nothing is known about the possible effects of UPD17 on embryo development, since this condition has never been described before.…”
Section: Introductionmentioning
confidence: 99%